Analisis Dana Kementrian Koperasi Dan UMKM Dalam Mengurangi Kemiskinan dan Penyerapan Tenaga Kerja Provinsi Banten: Analysis of the Ministry of Cooperatives and SMEs Funds in Reducing Poverty and Absorption of Labor in Banten Province - Yayah Rukayah (JOURNAL ISLAMIC ECONOMICS AD DIWAN, 2025)
Empowerment of Cooperatives and MSMEs in a structured and sustainable manner is expected to be able to harmonize the structure of the regional economy, and play a major role in accelerating regional economic growth, reducing unemployment rates, reducing poverty rates, dynamizing the real sector, and improving the distribution of community income. This research is motivated by the increase in poverty rates in Banten caused by a lack of employment opportunities, as well as the lack of quality human resources, especially regarding the level of poverty and employment in Banten Province. This study aims to analyze the effect of revolving funds on poverty reduction and increasing employment. The analysis methods used include partial tests (t-test), simultaneous tests (F-test), and coefficient of determination tests (R²). The results of the study indicate that partially, revolving funds have a significant effect on poverty reduction with a calculated t value > t table (2.601 > 2.030) and on increasing employment with a calculated t value > t table (3.872 > 2.030). Simultaneously, the revolving fund significantly impacted both variables, with a calculated F value > F table (4.437 > 4.15). The coefficient of determination indicates that the revolving fund contributed 13% to poverty reduction and 78% to employment growth. These findings empirically demonstrate that the existence of a revolving fund can encourage MSME development, optimize regional budget realization, and serve as an effective financial intermediation instrument in strengthening the regional and national economy as a whole.